ALTERNATIVE IMPROVEMENT OF SUBGRADE AND REINFORCEMENT OF EMBANKMENT ON PELABUHAN KUALA TANJUNG TOLL ROAD, INDERAPURA - KUALA TANJUNG SECTION IN NORTH SUMATRA (STA 0+000 S/D STA 3+500) - Agung Wahyu Eka Prasetya; Hutagamissufardal Hutagamissufardal (CERUCUK, 2021)
Planning the Kuala Tanjung Ruas Port of Inderapura - Kuala Tanjung Toll Road is one of the efforts to support economic growth in North Sumatra. The toll road will be built on a pile with a height of 2 ms / 9 m at STA 0 + 000 to STA 3 + 500. Due to limited land, the toll road section must be built on the poor subgrade. Based on the N-SPT test results, it is known that the subsoil consists of a clay layer with a thickness reaching 36 meters and a layer of sand at the top and bottom with a low N-SPT value. If the soft subgrade is burdened with a high heap, it is estimated that the subgrade will experience landslides, so it is necessary to plan the improvement of the subgrade and reinforcement of the pile.The soil improvement method chosen is the pre-loading method with a combination of the prefabricated vertical drain (PVD). Pre-loading method aims to spend the compression that occurs on the subgrade so that there is no compression during the service life of the road. The combination with PVD is intended to speed up the compression time in thick clay layers. The stability of the embankment will be calculated using a computer-assisted program, and geotextile reinforcement planning will be carried out if the value of the safety factor does not meet the requirements.Based on the analysis of compression computation will be divided into five zones. The amount of compression obtained under various piles of 2 ms / d 9 m was 2.25 m, 1.49 m, 1.75 m, 2.57 m, 3.65 m, 4.3 m, 4.69 m, and 5.06 m with an initial heap height of 5.02 m, 5.26 m, 6.51 m, 8.34 m, 10.41 m, 12.07 m, 13.46 m, and 14.83 m. Compression time required for subgrade is relatively long with a period of more than five years so that the planned acceleration with PVD. To accelerate the compression time to 5-6 weeks, a triangular PVD installation pattern is used with a spacing between PVD of 1.5 m and a depth of PVD installation as thick as a soft soil layer. From the results of the pile stability control, it is predicted that the pile will experience slides so that the reinforcement is installed with geotextile.Rp1.598,213,522,582.08.